Australia and the World Bank : Partnership Against Poverty in the Developing World - Conable, Barber B. (World Bank, Washington, DC, 2018)
Barber B. Conable, President of the World Bank Group addressed the topic of Australian International Development at the 1989 annual meetings. Poverty, and its persistence alongside such wellbeing, is both a moral outrage and a threat to security. The challenge of poverty is an economic, political and social one. Together, all those elements of change spell a single word: development, the priority business of the World Bank, the oldest, largest and still the most effective international agency in promoting development. But the Bank is only one of the forces fighting global poverty. More of it should come from nations like Australia. Targeted compensation programs can help see the poor through the extra impact of adjustment and keep their hopes and political patience alive. The Bank is supporting such efforts in Bolivia, Costa Rica, Ghana, Jamaica and Morocco and looking elsewhere to see how the timetable or scope of reforms can best be balanced.